Client Internal Factors to The Change of Upgrade, Downgrade, and Same Grade of Public Accounting Firm (An Empirical Study on The Banking Sector Companies Listed in The Indonesia Stock Exchange for The Year of 2014-2018) - Erma Setiawati; Devaria Aisya Setyowati; Mahameru Rosy Rochmatullah (Universitas Muhammadiyah Surakarta, 2020)
This study aimed at determining the effect of client internal factors, such as; firm size, financial distress and management changes to switching of a public accounting firm (PAF). The population of this study was the company of the banking sector listed in the Indonesia Stock Exchange from 2014 to 2018. The sampling technique used in this study was purposive sampling method which generated a sample of 195 companies. The multinomial logistic regression test was performed because there were three categories of the dependent variable. The results of the analysis revealed that financial distress did not affect the change of PAF upgrade, downgrade, and the same grade. Firm size did not affect the change of PAF upgrade, downgrade and the same grade and management changes did not affect the change of PAF upgrade, downgrade, and the same grade.